Effects of Saccharomyces boulardii cell wall polysaccharide on growth performance, immunity, antioxidant ability and ileal mucosal morphology of Jinhua weaned piglets in Northern Xinjiang region - Zhu, Wenshu; Mo, Xucheng; Zeng, Wenshuai; Ren, Wantong; Liu, Mengjian (Frontiers in Animal Science, 2025)
BackgroundThe high rates of diarrhea, mortality, and feed conversion ratio (F/G) among weaned piglets have significantly hindered the development of pig feeding practices in Jinhua, located in the North Xinjiang region. Saccharomyces boulardii cell wall polysaccharide (SBWP) is a probiotic that has the potential to enhance gastrointestinal immunity and health, while also reducing systemic inflammation, diarrhea rates, and mortality. This study investigates the effects of SBWP on the performance, immune capacity, antioxidant capacity, and mucosal morphology of weaned piglets from Jinhua, North Xinjiang region, through a 28-day feeding trial.MethodsA total of 64 male weaned Jinhua piglets, aged 28 days and with a mean body weight of 4.23 ± 0.53 kg, were utilized in this study. The piglets were randomly assigned to four experimental groups, each consisting of four pens with four piglets per pen, based on varying percentages of SBWP as a feed supplement. The supplementation concentrations for the four groups were 0% (control group), 0.2%, 0.5%, and 1.0% of SBWP, respectively.ResultsCompared to the CON group, the 0.5% and 1.0% SBWP groups demonstrated a increase in average daily feed intake (ADFI) and average daily gain (ADG), alongside a decrease in the feed-to-gain ratio (F/G). Additionally, the average fecal score and diarrhea frequency in the 0.5% and 1.0% SBWP groups were reduced, with no mortality recorded in these groups, which represented a 37.50% reduction compared to the CON group. In terms of ileal mucosal immunity, the 0.5% and 1.0% SBWP supplementation groups demonstrated reduced concentrations of pro-inflammatory cytokines, including interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α), as well as diamine oxidase (DAO). Conversely, both groups exhibited significantly elevated concentrations of the anti-inflammatory cytokine interleukin-10 (IL-10). Furthermore, the addition of 0.5% and 1.0% SBWP significantly increased secretory immunoglobulin A (SIgA). In serum immunity, both SBWP groups had reduced concentrations of TNF-α, IL-1β, IL-6 and DAO. Regarding the antioxidant capacity of the ileal mucosa, the content of malondialdehyde (MDA) and hydrogen peroxide (H2O2) in the 0.5% and 1.0% SBWP groups were decreased, while catalase (CAT), glutathione peroxidase (GSH-Px), and total antioxidant capacity (T-AOC) were increased, and superoxide dismutase (SOD) activity was enhanced. Lastly, the addition of 0.5% and 1.0% SBWP to the basal diet resulted in a promotion in villus height and the ratio of villus height to crypt depth (VCR), thereby improving the morphology of the ileal mucosa. In conclusion, the growth performance of weaned piglets from Jinhua in northern Xinjiang improved by 0.5-1.0% when supplemented with SBWP in the basal diet. This enhancement is attributed to the increased antioxidant capacity, improved immune function, enhanced mucosal morphology, and reduced concentrations of inflammatory factors in both the ileal mucosa and serum.